Gold nanoparticles for improved electron microscopic detection of Potato virus M in potato leaves and tubers - RAIGOND, BASWARAJ (Potato Journal, 2016)
The present study was aimed to develop immuno-gold electron microscopic technique to detect Potato virus M (PVM) in potato leaves and tubers. In-house raised antibodies against PVM was used for IgG purification and conjugated with colloidal gold (CG) nanoparticles for Electron microscopic detection of PVM. The EM studies revealed the presence of good concentrations of elongated particles coupled with several IgG conjugated gold nanoparticles either single or in small cluster indicating the presence of PVM. The cross reactivity and sensitivity of developed technique was examined by incubating with the pure cultures of PVY, PVS, PVA, PVX and PVM. Wherein, it revealed that only homologous virus (PVM) was decorated but not with other viruses. The technique was validated by incubating it with suspected potato leaf samples collected from field. It was parallel confirmed by RT-PCR wherein, the technique supplemented the developed technique. The technique was further extended to detect PVM in potato tubers where, elongated virus particle coupled with gold nanoparticles was observed revealing the presence of Potato virus M in potato tuber. Hence, this study describes a useful method that allows us for same day diagnosis and contributes significantly towards a rapid and clear identification of PVM in potato leaves and tubers.